ANALYSIS OF NEEDS FOR THE DEVELOPMENT OF NUMERICAL LITERATURE ASSESSMENT FROM MATHEMATICS LEARNING OUTCOMES REVIEWED FROM PEDAGOGIC PERSPECTIVE - Indra Gunawan; Babang Robandi (xxxx-xxxx, 2022)
The results of the Program for International Student Assessment (PISA) on a regular basis which have implications for the Computer-Based National Assessment Program (ANBK) which will be implemented by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia in 2021, make improvements to the mathematics learning assessment instrument through findings. The results obtained from the field test results are considered important to be carried out. This study aims to describe the need for a Numerical Literacy Assessment of Mathematics Learning Outcomes that trains five competencies in learning mathematics, namely problem solving (problem solving), communication (communication), reasoning (reasoning), connection (connection), and representation (representation) by considering pedagogical study. This study involved 10 teacher respondents from several regions in Indonesia. The instrument of this research was a questionnaire and an observation guide to the evaluation of mathematics learning outcomes made by teachers which had been validated by two pedagogic experts and a mathematician. The questionnaire was distributed openly through the google form application. The questionnaire data was processed qualitatively, followed by data reduction, data presentation, discussion and discussion and conclusions. The results of this study include the evaluation instruments made by the teacher are still dominated by multiple choice questions and objective descriptions, respectively 80 and 85% and the finding of the need for improvement in connection competence and mathematical representation which is at the 45% level. . In relation to pedagogy, this needs analysis is considered necessary because the four aspects of evaluation are considered necessary to be applied.